Pengaruh Kepemimpinan Kepala Madrasah Terhadap Mutu Pendidikan - Nurpadillah Nurpadillah; Syahril Syahril; Fitriani Fitriani (Institusi Agama Islam Negeri (IAIN) Bone, 2024)
The study discusses the influence of the leadership of the Chief Madrasah on the quality of education in the A-Hidayah Bakke MTs. As for the usefulness of the research carried out, it is scientific and practical. Subjects in this study were students 73 and teachers 14 a total of 87. The data collection technique used is the lifting and documentation technique, which is a method used by arriving at the research site, and holding direct observations of the object being studied. The type of research carried out is quantitative research in particular correlational research, using pedagogical and psychological management approaches. The data analysis technique is Microsoft Excel. Based on the results of the analysis and interpretation presented the result that it is based on the statistical test T value t count of 0.567 greater than the t value of table 0.207, then it can be concluded that there is a influence of the leadership of the head of the matrasah (X) on the quality of education (Y). It is based upon the result of the simple linear regression analysis with the help of microsoft word and referring to the correlation value between X and Y is 0.314. Included in the middle category. The determination coefficient value is 0.314 or 31.4%. Which means that X can explain the big Y. The remaining 31.4% is influenced by other factors. Significant value < alpha = 0.05. So the final result is that the leadership variable of the head of the madrasah affects the educational quality variable by 31.4%, while the remaining 68.6% is affected by another factor.